The relationship between physical activity, physical health, and mental health among older Chinese adults: A scoping review - Wong, Ming Yu Claudia; Ou, Kai-ling; Chung, Pak Kwong; Chui, Kei Yee Katie; Zhang, Chun-qing (Frontiers in Public Health, 2023)
The aging Chinese population is growing fast, and the proportion of the population aged 60 years old is projected to reach 28% by 2040, estimated 402 million. With increased life expectancy, the aging population tends to suffer from health risks and diseases, which create a burden on public health policy. Hence, it is essential to promote healthy and active aging, which includes improving older adults' physical and mental capacities and advocating for the achievement of a healthy life expectancy. Despite the rapidly growing aging population in China, there have been no reviews investigating the effect of physical activity on physical and mental health among older Chinese adults. Therefore, the current study aimed to review studies from the past 15 years that illustrate the effect of physical activity on physical and mental health among Chinese older adults. Based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews (PRISMA-ScR), this review addresses the associations between physical activity, physical health and mental health among older Chinese adults. A total of 371 studies were included in the scoping review, which covered the relationships between physical activity, physical health and mental health variables. The scoping review also revealed the impact of various kinds of physical activity affecting older adults' physical health, such as functional fitness, body composition, fall risk and balance, and mental health issues, such as depression, anxiety, cognitive function and quality of life. Moreover, studies have identified innovative forms of physical activity as emerging trends in physical activity interventions for older adults. To conclude, this scoping review captured the common effects between physical activity and overall wellbeing, including physical, mental, and cognitive health. Additionally, diverse forms of physical activity intervention, such as group-based and supervised individual interventions, should be supported, and cross-cultural exercise comparisons should be made in future explorations.